TRADISI MALEMAN di Masjid Agung Demak - Anafah, Naili (Sabda: Jurnal Kajian Kebudayaan, 2008)
Maleman is one tradition performed by Moslem communities in Demak, a coastal city in Central Java. This paper aims at describing activities of Maleman as practiced by pilgrimers by staying at Masjid Agung Demak, Demak Great Mosque, on the last nights of uneven dates of Ramadhan fasting month. The purpose of this practice is to expect for the nights of the Lailatul Qodar which is believed as heavenly mercyful nights in which heavens of Allah are filled with blessings and mercies. Activities of maleman at Masjid Agung Demak area are different from those of maleman at other mosque areas; nowadays maleman at Masjid Agung Demak area is accompanied with night market, festival of rebana, carnival on the street, exchange meal, fire crackers and other secular interests.